2013
DOI: 10.1159/000345984
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dementia in Elderly Clients of a Private Health Care Plan: A Study of the FIBRA-RJ, Brazil

Abstract: Aims: To describe the overall prevalence of dementia syndrome and its major subtypes among elderly clients of a private health care plan and to ascertain the association between this syndrome and socioeconomic characteristics. Methods: A survey was organized in two stages: screening for cognitive impairment and diagnostic evaluation. The study population comprised 683 elderly subjects (aged >67 years), an expanded sample of 7,486 individuals, of the database of the FIBRA-RJ, which evaluated clients of a privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 61 publications
0
29
2
5
Order By: Relevance
“…Over the last two decades, there have been modest but significant advances in the pharmacological treatment of this devastating condition. However, effective management and treatment to delay disease progression requires early and accurate diagnosis of dementia at its earliest stages [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, there have been modest but significant advances in the pharmacological treatment of this devastating condition. However, effective management and treatment to delay disease progression requires early and accurate diagnosis of dementia at its earliest stages [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…Longer life has an associated risk of physiological decline in body functions and, because of this, increases the probability of chronic or debilitating diseases occurring, such as dementia, the prevalence of which increases with age, although it is not a normal aspect of aging (WHO, 2017). In FIBRA-RJ, the prevalence of dementia was 16.9 and proved to be associated with advanced age and a low level of schooling (Ribeiro et al, 2013). It is worth noting that the Finnish study concluded that there is a reduced effect of the elderly's schooling on the FAQ results, although this effect was not enough to change the established cut-off point (Juva et al, 1997).…”
Section: Discussionmentioning
confidence: 95%
“…The differences between the results of this study and those of the studies cited previously may be due to the diagnostic method of dementia adopted as a gold standard by this study, completed after two meetings of consensus between a neuropsychologist -who administered various cognitive and functional evaluation tests -and two geriatricians -who evaluated clinical history, and physical, laboratory and imaging exams, considering criteria in the Diagnostic and Statistical Manual of Mental Disorders IV (APA, 2000), as detailed in a previous publication (Ribeiro, Lopes, & Lourenço, 2013). The other studies used the evaluation of only one neurologist physician, based only on cognitive and functional tests to establish the diagnosis of dementia (Juva et al, 1997;Cruz-Orduña et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…O estudo FIBRA-RJ, deu origem a uma série de artigos, dissertações de mestrado e teses de doutorado. 3,12,[28][29][30][31][32][33][34][35][36] Discussão O estudo FIBRA-BR, por seu delineamento multicêntrico, provavelmente representou um dos esforços mais abrangentes de pesquisadores brasileiros, para a compreensão da dimensão da fragilidade e seus fatores associados, em território nacional. O segmento Rio de Janeiro desse estudo, o FIBRA-RJ, representou uma tentativa de ir além dos objetivos inicialmente traçados, e dar continuidade ao acompanhamento da amostra examinada, investigando outros aspectos de acometimento de saúde, bastante comuns entre a população idosa, e ainda carentes de estudos populacionais com um número substancial de indivíduos.…”
Section: Resultsunclassified